To simplify the expression \( 2(k - 4) - 3(2k - 1) \), we will expand both terms and then combine like terms.
-
Distributing the \( 2 \) in the first term: \[ 2(k - 4) = 2k - 8 \]
-
Distributing the \( -3 \) in the second term: \[ -3(2k - 1) = -6k + 3 \]
-
Now, combine these results: \[ 2k - 8 - 6k + 3 \]
-
Combine the like terms:
- Combine \( 2k \) and \( -6k \): \[ 2k - 6k = -4k \]
- Combine \( -8 \) and \( +3 \): \[ -8 + 3 = -5 \]
-
Putting it all together, we have: \[ -4k - 5 \]
Therefore, the final answer is: \[ \boxed{-4k - 5} \]